Potential interaction between lysophosphatidic acid and tumor-associated macrophages in ovarian carcinoma - Ying Feng; Meizhu Xiao; Zihan Zhang; Ran Cui; Xuan Jiang; Shuzhen Wang; Huimin Bai; Chongdong Liu; Zhenyu Zhang (BMC, 2020)
Abstract Ovarian carcinoma is the deadliest type of gynecological cancer. The unique tumor microenvironment enables specific and efficient metastasis, weakens immunological monitoring, and mediates drug resistance. Tumor associated macrophages (TAMs) are a crucial part of the TME and are involved in various aspects of tumor behavior. Lysophosphatidic acid (LPA) is elevated in the blood of ovarian carcinoma patients, as well as in the tumor tissues and ascites, which make it a useful biomarker and a potential therapeutic target. Recent studies have shown that LPA transforms monocytes into macrophages and regulates the formation of macrophages through the AKT/mTOR pathway, and PPAR γ is a major regulator of LPA-derived macrophages. In addition, TAMs synthesize and secrete LPA and express LPA receptor (LPAR) on the surface. With these data in mind, we hypothesize that LPA can convert monocytes directly into TAMs in the microenvironment of ovarian cancer. LPA may mediate TAM formation by activating the PI3K/AKT/mTOR signaling pathway through LPAR on the cell surface, which may also affect the function of PPAR γ, leading to increased LPA production by TAMs. Thus, LPA and TAMs form a vicious circle that affects the malignant behavior of ovarian cancer.